Analyze of Frequency Selective Surfaces By Hybrid MOM-PO-GTD Method - samir Mendil; Aguili taoufik (Universitas Diponegoro, 2020)
The intent of this article is to analyze the Diraction phenomena of the incoming waveand provide a new Approach for analyzing the frequency selective surface (Fss) by usinga hybrid method combining Moment Method (MoM), optical physics (PO) with Generaltheory of Diraction (GTD). the frequency selective surface (Fss) is a periodic surfacewith identical two-dimensional arrays of elements arranged on a substrate dielectric. Anincoming plane wave will either be transmitted (bandwidth) or re ected (stopband),completely or partially, depending on the nature of the array element. This happenswhen the frequency of the electromagnetic (EM) wave correspond with the resonantfrequency of the FSS elements. Hence, in free space, and for a certain frequency range,an FSS is capable of transmitting or blocking EM waves; therefore, identied as spa-tial lters. Today, FSSs have been extensively studied and there is tremendous growthin its design and implementation for dierent applications at the microwave to opticalfrequency ranges. In this review article, we present a new hybrid method form on Mo-ment method and GTD for analyzing dierent categories of FSS based on the design ofthe structure, the array elements used, and applications. We also focus on the eectsof diraction, methodology, experimental verications of design examples, as well ason prospects and challenges, particularly in the microwave regime. We highlight theirimportant performance metrics, especially with regard to progress in this area couldfacilitate advanced electromagnetic innovation.